2023
DOI: 10.22517/23447214.24792
|View full text |Cite
|
Sign up to set email alerts
|

Diseño y construcción de un sistema de seguimiento solar para un prototipo de colector cilindro-parabólico

Brayan Eduardo Tarazona-Romero,
Arly Darío Rincón Quintero,
Javier Gonzalo Ascanio Villabona
et al.

Abstract: La búsqueda de alternativas tecnológicas para satisfacer diversas necesidades globales, ha desencadenado un arduo proceso de investigación y desarrollos tecnológicos a nivel mundial para el aprovechamiento de los recursos renovables. Por su parte, los colectores lineales cilindro-parabólicos, han demostrado ser una alternativa para realizar el proceso de calentamiento de agua y para la producción de energia eléctrica. Por su parte, el grupo de investigación en sistemas de energia, automatización y control (GIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In turn, the DNI in W/m2 corresponding to the prototyping implementation site must be provided, as well as the number of sun rays. In previous works, Tarazona-Romero et al [12] developed a study to determine the performance of a prototype CFL collector at the Technological Units of Santander. The authors carried out a previous traditional study and indicated that the average DNI in the area is 600 W/m2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, the DNI in W/m2 corresponding to the prototyping implementation site must be provided, as well as the number of sun rays. In previous works, Tarazona-Romero et al [12] developed a study to determine the performance of a prototype CFL collector at the Technological Units of Santander. The authors carried out a previous traditional study and indicated that the average DNI in the area is 600 W/m2.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, 3D CSPs operate on the point concentration principle and are divided into two technologies [11]; (i) dish-striling and (ii) concentrating tower. The CCPs have single-axis solar tracking systems [12], [13], which ensure year-round utilization of the DNI [14]. The operation of the system is simple, the heat from the DNI is concentrated and transfers to a heat transfer fluid that is fed into a thermodynamic cycle to produce useful energy [15].…”
Section: Introductionmentioning
confidence: 99%